Spontaneous Ipsilateral Ectopic Pregnancy in the Tubal Stump of Previous Partial Salpingectomy - Cooper, Sian (Nepal Journal of Obstetrics and Gynaecology, 2013)
We present an unusual case of recurrent ectopic pregnancy in the tubal stump of a previous partial salpingectomy. The patient presented with the classic triad of amenorrhoea, per vaginal bleeding and abdominal pain paired with a void uterus on ultrasonography. Her history was notable for a previous ectopic pregnancy resulting in a laparotomy and salpingectomy-oophrectomy. A positive B-hCG and echogeneic areas in the right adnexa led to a diagnosis of recurrent ectopic pregnancy. On laparotomy, an ectopic pregnancy was found in the right tubal stump. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 50-52 DOI: http://dx.doi.org/10.3126/njog.v7i1.8837